(untitled) (Research, Society and Development, 2018)
In this paper we present and discuss some themes about school learning assessment that have been the focus of researches developed in preservice teacher who teaches mathematics education. Using some Content Analysis guidelines, we carry out analysis of researches available in Brazilian Digital Library of Theses and Dissertations. Through analysis, we highlight the following themes: preservice teachers’ vision, conception or understanding of assessment; prospective teachers’ familiarity with assessment tools; assessment practices during preservice teacher education. About each of these themes, in general, we could notice that: vision, conception or understanding of many preservice teachers about assessment is related to some of the purposes that it can have; prospective teachers are more familiar with the written test, feeling insecure with other instruments; assessment practices during preservice teacher education are restricted to a few instruments, almost exclusively to the written test, and prospective teachers often unknown the professors’ assessment or correction criteria when they use this or any other instrument. In identifying these aspects, we hope contribute to formative actions and future investigations in the field of Mathematics Education.